Aplikasi Crowdfunding Sebagai Perantara Penggalangan Dana Berbasis Website dan Facebook Application - Rosalina Rosalina; Andreas Handojo; Adi Wibowo (Jurnal Infra, 2015)
To realize an idea, either for business or social purposes wouldrequire a lot of things, such as funding and publication. Fundraising itself is not quick and easy, it takes a lot of people(crowd) to raise funds quickly. Moreover, gathering a lot ofpeople needs publications that generally use social media. Thisresearch is intended to create application that can meet theserequirements, which is a fundraising application that applying the concept of crowdfunding and is connected to social media - Facebook.This application is a web-based application and can be accessed from Facebook Application. Another publications features are login with Facebook, share to Facebook, and newsletter features. From the results of the implementation and testing, we can conclude that this system is capable of running its function as fundraising intermediaries and also publish a fundraising project via Facebook and newsletter.